When i was your age eaudiobook Life lessons, funny stories & questionable parenting advice from a professional clown. - Thompson, Kenan (HarperAudio, 2023)
"Kenan is a master storyteller with extraordinary stories to tell. I wouldn't miss this for the world."—Leslie Jones When I Was Your Age is a hilarious, heartwarming and surprising ode to growing up, getting older and wiser, and luck, life, and learning from the school of hard knocks, from SNL's longest-serving actor, Kenan Thompson Kenan Thompson is Saturday Night Live's longest-ever-serving cast member and a star of such pioneering sketches as "Black Jeopardy" and is hugely beloved thanks to a tidal wave of nostalgic fans who grew up on early 2000s classics All That, Good Burger, and Kenan & Kel on Nickelodeon. He's also a dad (to two girls) in his mid-40s living in suburbia, and whose universal, relatable, family-friendly humor has created unbelievable appeal and engagement from fans from middle America to coastal elites. Becoming a dad sucked the cool right out of him — and he's OK with that! When I Was Your Age is packed with hilarious yet poignant essays that are aimed to offer any reader valuable advice on parenting, focusing on positivity, and having fun in life. Kids, new parents, fellow fathers, budding comics, and aunties who want to pinch his cheeks, can all learn from his biggest mistakes and most triumphant victories. There's something for everybody here!